Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For a vector $X$ which follows a multinomial Gaussian distribution $N(\vec{0},\Sigma)$, a given vector $b$, and a known scalar value $c$, I would like to calculate the expectation :

$E[X|X^Tb = c]$

That is the expected value of the multivariate variable $X$ given that it will lie on the plane $ X^Tb = c$. I have tried by parametrizing $X$ as $X = \vec{a_0} + t_1 \vec{a_1} ... t_{n-1} \vec{a_{n-1}}$ and calculating the integral $\int_{-\infty}^{\infty} ... \int_{-\infty}^{\infty} xf(x) dt_1 ... dt_{n-1}$, where $f(x)$ is the pdf of the Gaussian, but I end up with an extremely messy formula even when trying to solve in the simple three-dimensional case.

My question is whether there is a known closed form solution for the above expectation and/or if there is a specific parametrization I could use to simplify the solution.

share|improve this question
The conditional distribution of $X$ will also be a multinomial Gaussian distribution so you can look for the conditional mode which will be the conditional expectation. You can use Lagrange multipliers for this. stats.stackexchange.com/a/9073/2958 is slightly related –  Henry Oct 12 '12 at 21:17

1 Answer 1

Let $Y=X_k$ for some fixed $k$, and $Z=X^Tb$. Then $(Y,Z)$ is a two-dimensional centered gaussian vector hence a general result is that $\mathbb E(Y\mid Z)=a\cdot Z$ for a suitable scalar $a$. Note that $\mathbb E(YZ)=\mathbb E(\mathbb E(Y\mid Z)Z)$ hence $\mathbb E(YZ)=a\cdot\mathbb E(Z^2)$, and $\mathbb E(Y\mid Z)=\mathbb E(Z^2)^{-1}\mathbb E(YZ)\cdot Z$. Using this for every $k$ yields $\mathbb E(X\mid Z)=\mathbb E(Z^2)^{-1}\mathbb E(XZ)\cdot Z$.

In the present case, $\mathbb E(XZ)=\mathbb E(XX^Tb)=\Sigma b$ and $\mathbb E(Z^2)=b^T\mathbb E(XX^T)b=b^T\Sigma b$. This can be summarized as $$ \mathbb E(X\mid X^Tb=c)=\lambda\cdot\Sigma b,\quad\text{where}\quad\lambda=\frac{c}{b^T\Sigma b}. $$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.